ANALISIS RESEPSI KHALAYAK TERHADAP MAKNA BODY POSITIVITY PADA INSTAGRAM TARA BASRO - Milatishofa, Milatishofa; Kusrin, Kusrin; Arindawati, Weni Adityasning (Linimasa : Jurnal Ilmu Komunikasi, 2021)
This study aims to see how the public understands and interprets the application of a body positivity carried out by Tara Basro on March 3, 2020 which is uploaded to her Instagram account. The reason researchers took this topic was because of the controversy that arose first, government agencies labeled it inappropriate. This study used a qualitative approach with Stuart Hall's reception analysis method and data analysis techniques in the form of in-depth interviews. The differences in the background of the informants' religious and cultural norms affect their acceptance. The results of this study, the informants interpreted body positivity of the body carried out by Tara Basro through her Instagram upload in the form of self-appreciation and giving her followers an understanding that everything that is owned by the body must be accepted as it is with gratitude.